2009
DOI: 10.1007/s00411-008-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electron and gamma irradiation on the induction of micronuclei in cytokinesis-blocked human blood lymphocytes

Abstract: The effect of electrons and gamma irradiation on the induction of micronuclei in cytokinesis-blocked human peripheral blood lymphocytes was investigated to understand the relative biological effectiveness (RBE) of electrons compared with gamma rays. Blood samples were irradiated with an 8 MeV pulsed electron beam, at a mean instantaneous dose rate of 2.6 x 10(5) Gy s(-1). Gamma irradiation was carried out at a dose rate of 1.98 Gy min(-1) using (60)Co gamma source. A dose-dependent increase in micronuclei yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Micronucleus frequency in lymphocytes exposed to low LET radiation such X-rays, gamma rays, and electron beams increases linearly-quadratically with the absorbed dose, indicating a contribution of both single and multi-track lesions (16,25,26). Therefore, MN frequency is clearly infl uenced by dose rates.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Micronucleus frequency in lymphocytes exposed to low LET radiation such X-rays, gamma rays, and electron beams increases linearly-quadratically with the absorbed dose, indicating a contribution of both single and multi-track lesions (16,25,26). Therefore, MN frequency is clearly infl uenced by dose rates.…”
Section: Discussionmentioning
confidence: 94%
“…Our earlier dose-effect study using 8 MeV electrons revealed that the response of MN was linear-quadratic in nature (16). Since the quadratic (b) coeffi cient of the dose-response curve is dose-rate-dependent and dose assessment is done using dose-response parameters, it is essential to have data for a wide range of dose rates, particularly those encountered in the working environment.…”
mentioning
confidence: 99%
“…Micronuclei are markers of DNA damage and are commonly used to measure RBE. Micronuclei frequency has been used as a biological endpoint to predict electron RBE as 1.1–1.3 across three studies 22 24 for electrons in the 1.5–8 MeV. Cell types measured were human lymphocytes and an ovarian cancer cell line.…”
Section: Discussionmentioning
confidence: 99%
“…All selected calibration curves were compared using two approaches: 1) the parameters of each methodology, as well as dicentrics distribution data with no modifications; and 2) all data (including statistic coefficients) were standardized using Dose Estimate software (Ainsbury et al, 2010) to perform the statistics. Thus, all results were retested to analyze their conformity with Poisson distribution by means of the Papworth's u test (Acharya et al, 2009;IAEA, 2011). Thereafter, using R-based tools2 (R Development Core Team, 2012) the Pearson's Chi-squared test was applied to determine whether the yield of dicentric varies according to calibration curves.…”
Section: Comparison Of Calibration Curvesmentioning
confidence: 99%